Strategies for college writing sentences, paragraphs, essays - Harris, Jeanette 1936- (Allyn and Bacon, 2000)
Strategies for College Writing offers full coverage of the basics of writing essays, paragraphs, and sentences with a focus on preparing students for academic writing and reading assignments. The book starts with detailed attention to the writing process at a pace that is comfortable for the developmental student. It emphasizes the importance of the controlling idea, the process of gathering information from both personal experience and other sources, the structure of an essay, and the way in which ideas are arranged and connected. In Part Two, students learn how to use models for each of the patterns of development. The sentence/grammar material is self-contained in Part Three for flexible use by students studying independently or by teachers who might want to focus on a particular topic. Students learn how to construct different types of sentences and how to use appropriate punctuation. Ample exercise material reinforces the instruction. Part Four, Critical Reading Strategies, focuses on the process of reading and relates it to the process of writing and provides students with effective strategies for summarizing, note-taking, and annotating reading material.